Admission glucose level and short-term mortality in older patients with acute myocardial infarction: results from the KORA Myocardial Infarction Registry. Issue 6 (3rd June 2021) - Mamadjanov, Temur; Volaklis, Konstantinos; Heier, Margit; Freuer, Dennis; Amann, Ute; Peters, Annette; Kuch, B; Thilo, Christian; Linseisen, Jakob; Meisinger, Christa
Abstract : Study objectives: To investigate the association between admission blood glucose levels and 28-day mortality as well as in-hospital complications in older patients with incident acute myocardial infarction (AMI) undergoing modern treatment. Methods: From a German population-based regional MI registry, 5530 patients (2016 women), aged 65–84 years, hospitalised with an incident AMI between 1 January 2009 and 31 December 2016 were included in the study. Multivariable logistic regression models were used to assess the associations between admission blood glucose and 28-day mortality as well as in-hospital complications after AMI. Analyses stratified according to age, diabetes and type of infarction (ST-elevation MI (STEMI)/non-STEMI) were conducted. Results: The adjusted ORs for the association between admission blood glucose and 28-day mortality in young-old (65–74 years) and old (75–84 years) patients with AMI were 1.40 (95% CI: 1.21 to 1.62) and 1.21 (95% CI: 0.98 to 1.50) per 1 SD increase in admission blood glucose, respectively. Furthermore, higher admission blood glucose was related to case fatality irrespective of the diabetes status and type of infarction only in the under-75 group. For the patients aged 75–84 years, it was only true for those without diabetes and STEMI. Admission blood glucose was also associated with major cardiac complications in both age groups. Conclusion: Admission blood glucose was significantly associated with 28-day case fatality in patients with AMI aged 65–74 years but not 75–84 years; furthermore, in both age groups there was an increased risk of major complications. It seems that admission glucose may play a rather minor role in terms of case fatality in higher aged patients with AMI.